CROSS-CULTURAL LITERACY AS AN INDICATOR OF SOCIO-CULTURAL DEVELOPMENT OF THE INDIVIDUAL - L. Sayenko; L. Kuvaeva (Вестник Северо-Кавказского федерального университета, 2022)
The article presents an analysis of the concepts of «literacy», «cultural literacy», «intercultural literacy». The common, uniting components of these concepts are highlighted. The process offormation of intercultural literacy of students is presented as a means of understanding and accepting cultural identity, the basis for the formation of cultural experience and the ability to cultural dialogue. The authors note that the intercultural literacy of an individual is realized at several levels: the individual (personal), the family, of the educational organization, of the education system. The educational activities that contribute to the formation of intercultural literacy are considered. It is concluded that the level of development of intercultural literacy determines the level of sociocultural development of the individual.